Incorporating multiple intelligences into advisement of theatre students - Bailey, Sally D. (My University, 2009)
If, as Gardner maintains, education is the development of understanding: a way of thinking about and solving problems within the disciplines and domains being studied (Gardner, 2006), faculty advisors need to guide students into courses within their curriculum which provide access to the thinking skills necessary for success in the workplace and allow them to understand and function within the wider global community beyond their 9 to 5 jobs. The global workplace is currently undergoing a major paradigm shift into what Daniel Pink calls “The Conceptual Age,” which will require a new way of functioning on the job by incorporating the ability to understand and use design, story, synthesis, empathy, play, and meaning (Pink, 2006). The Multiple Intelligences developed by a general undergraduate theatre curriculum incorporates all of these abilities, positioning theatre majors to become potential leaders in the 21st century workplace whether they end up as theatre artists or in other professions. Our job as theatre faculty is to communicate our curricular strengths as embodied in the intelligences of our discipline not only to our students, but to the entire university in order to position ourselves in the central hub of education. We have more to offer our institutions and the wider culture, than we previously acknowledged.
Keywords: Multiple intelligences; Student advisement; Daniel Pink; Gardner, Howard; Storytelling; Play